Peran Sat Intelkam dalam Penggalangan Organisasi Masyarakat Uslam Nasional untuk Mencegah Radikalisme - Farros Oktorofi (Indonesian Journal of Police Studies, 2020)
This research is motivated by the not yet maximum mobilization of Nationalist Islamic Organizations such as NU and Muhammadiyah in an effort to prevent radical Islamic movements in the Cimahi Regional Police Legal Area. Even though the strength of these mass organizations can prevent the radical Islamic Movement of Pro-violence and Pro-intolerance in the Legal Area of Cimahi Regional Police. The rise of the radical Islamic movement is marked by the emergence of names from the region which are already joined by a large terrorist group network and have even become suicide bombing actors, the existence of FPI and HTI mass organizations, and the emergence of lone wolf cases. Therefore, a study was carried out aimed at finding out the picture of raising Islamic Nationalist Organizations in the Legal Area of the Cimahi Regional Police conducted by Satintelkam, describing the implementation of Polmas Model B by Satintelkam, as well as the factors affecting the policy environment.This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques with interviews, observations, and document studies.The results of the study found that the Nationalist Islamic Community Organizations Organization which was analyzed by Law No. 16 of 2017 Article 40 found that the implementation of Community Organizing had been carried out but not yet optimal. However, if the Nationalist Islamic Community Organization is analyzed using National Police Chief Regulation No. 3 of 2015 Article 11 regarding the implementation of Model B Polmas through intensification of the activities of the police technical functions, it is found that the Police intelligence intelligence unit has not understood the procedures for implementing Polmas Model B through its units because SOPs and lack of socialization. While the inhibiting factors are political, technological, social and natural weather factors. While the supporting factors are culture, economy, history and other policies.Based on the results of the study, the authors suggest several things, namely socialization of community policing, completing SOPs, adding and placing personnel according to the needs of the number and ability, increasing the ability of media technology, and reviving Kominda cooperation.